PENGARUH KONFLIK PEKERJAAN KELUARGA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH KOMITMEN AFEKTIF DI KANTOR PAJAK PELAYANAN PRATAMA KOTA BANDA ACEH - Siti Fathia Zahra; Nur Chalil (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
Abstract: The purpose of this study is to measure the effect of Work-Family Conflict and Job Satisfaction toward Employee Performance mediated by Affective Commitme. The sample consist of 103 employees of the Banda Aceh City Primary Service Tax Office. The sampling technique uses nonprobability sampling and the type of  sampling is total sampling. Data was collected through survey using questionnaire. The Hierarchical Linear Modelling is used on analytical method to determine the effect of variables involved. The result shows that Work-Family Conflict are not significant to affective commitment and employee performance, Job Satisfaction has a significant effect on Affective Commitment and Employee Performance, the affective commitment has a significant effect on employee performance, and Affective Commitment does not play a mediating role in the influence between Work-family Conflict and Job Satisfaction on Employee Performance.